The efficacy of 5-aminolevulinic acid photodynamic therapy for pediatric vulvar lichen sclerosus - Shan Zhang; Yukun Wang; Juncheng Wang; Jie Liu (Photodiagnosis and Photodynamic Therapy)
Background: Prepubertal girls are one of the vulnerable populations of vulvar lichen sclerosus (VLS), which results in a decreased quality of life and increases risk of vulvar cancer. But the therapeutic effects of traditional topical remedies are unsatisfactory in some pediatric patients. 5-Aminolevulinic acid photodynamic therapy (ALA-PDT) is an effective treatment for refractory VLS patients, but no study has been conducted in child patients. Methods: The patients included in this study underwent three sessions of ALA-PDT at 2-week intervals. All patients were evaluated for objective clinical appearances and subjective symptoms quantitatively. Statistical analysis comparing parameters at baseline and after three-time ALA-PDT was performed. Results: A total of seven VLS girl patients were included in this study. Both primary objective appearances (lesion size and depigmentation) and subjective symptoms (itching and burning pain) were improved remarkably after the third treatment. Besides, adverse effects, mainly as pain and post-treatment edema, were mild and could be tolerated. Conclusions: ALA-PDT is an effective and safe therapeutic option for VLS girl patients. Compared with adult patients, the symptoms resolved more quickly in child patients.